Donor plasmids for phenotypically neutral chromosomal gene insertions in Enterobacteriaceae. Issue 12 (23rd December 2020) - Holden, Emma R.; Wickham, Gregory J.; Webber, Mark A.; Thomson, Nicholas M.; Trampari, Eleftheria
Abstract : Recombineering using bacteriophage lambda Red recombinase (λ-Red) uses homologous recombination to manipulate bacterial genomes and is commonly applied to disrupt genes to elucidate their function. This is often followed by the introduction of a wild-type copy of the gene on a plasmid to complement its function. This is often not, however, at a native copy number and the introduction of a chromosomal version of a gene can be a desirable solution to provide wild-type copy expression levels of an allele in trans . Here, we present a simple methodology based on the λ-Red-based 'gene doctoring' technique, where we developed tools used for chromosomal tagging in a conserved locus downstream of glmS and found no impact on a variety of important phenotypes. The tools described provide an easy, quick and inexpensive method of chromosomal modification for the creation of a library of insertion mutants to study gene function.